The relation between quantum and classical field theory with a classical source: Field theory with a classical source - Fulling, S. A.; Landulfo, A. G.S.; Matsas, G. E.A. [UNESP] (The Royal Society, 2020)
Classical field theory is about fields and how they behave in space-time. Quantum field theory, in practice, usually seems to be about particles and how they scatter. Nevertheless, classical fields must emerge from quantum field theory in appropriate limits, and Michael Duff showed how this happens for the Schwarzschild solution in perturbative quantum gravity. In a series of papers, we and others have shown how classical radiation from an accelerated charge emerges from quantum field theory when the Unruh thermal effect is taken into account. Here, we sharpen those conclusions by showing that, even at finite times, the quantum picture is meaningful and is in close agreement with the classical picture.
Keywords: acceleration; bremsstrahlung; horizon; Rindler space; Unruh effect